Expose or protect? A randomized controlled trial of exposure in vivo vs pain-contingent treatment as usual in patients with complex regional pain syndrome type 1. Issue 10 (October 2016) - den Hollander, Marlies; Goossens, Mariëlle; de Jong, Jeroen; Ruijgrok, Joop; Oosterhof, Jan; Onghena, Patrick; Smeets, Rob; Vlaeyen, Johan W. S.
Abstract : Abstract: Complex regional pain syndrome type I (CRPS-I) highly affects patients' ability to perform daily life activities. Pain-related fear might be a key target to reduce disability in chronic pain. Current treatments aiming at reducing pain show little improvements on pain and disability, whereas novel exposure-based treatments targeting pain-related fears have shown to be promising. We conducted a randomized controlled trial (N = 46) comparing exposure in vivo (EXP) with pain-contingent treatment as usual (TAU), for CRPS-I patients with at least moderate levels of pain-related fear. Primary outcome is self-reported disability, for upper and lower extremity, respectively. Secondary outcomes are self-reported pain-intensity, pain-catastrophizing, perceived harmfulness of physical activity, and health-related quality of life. Pretreatment to posttreatment and pretreatment to 6-month follow-up change scores were tested using randomization-based inference. EXP was superior to TAU in reducing upper extremity disability from pretreatment to posttreatment (between-group difference, 1.082; 95% confidence interval [CI], 0.563-1.601; P < 0.001) and from pretreatment to 6-month follow-up (1.303; 95% CI, 0.917-1.690; P < 0.001). EXP was superior in reducing lower extremity disability from pretreatment to 6-month follow-up (3.624; 95% CI, 0.467-6.781; P = 0.02), but not from pretreatment to posttreatment (3.055; 95% CI, −0.018 to 6.128; P = 0.054). All secondary outcomes significantly favored EXP pretreatment to posttreatment, as well as pretreatment to 6-month follow-up. Exposure to daily activities shows to be more effective than a protective pain-contingent TAU in reducing self-reported disability in daily life of CRPS-I patients with at least moderate levels of pain-related fear. Abstract : In CRPS-I patients with at least moderate levels of pain-related fear, exposure to daily activities is more effective than a pain-contingent treatment in reducing disability.Supplemental Digital Content is Available in the Text.